\(\dfrac{a}{7}-\dfrac{1}{4}=\dfrac{1}{b}\)
\(\dfrac{4a-7}{28}=\dfrac{1}{b}\)
⇒(4a-7).b=1.28
(4a-7).b=28
⇒4a-7 và b ∈ Ư(28)={-28;-14;-7;-4;-2;-1;1;2;4;7;14;28}
Ta có bảng:
4a-7=-28 thì b=-1
a=-21/4 (loại)
4a-7=-1 thì b=-28
a=3/2 (loại)
4a-7=-14 thì b=-2
a=-7/4 (loại)
4a-7=-2 thì b=-14
a=5/4 (loại)
4a-7=-7 thì b=-4
a=0 (t/m)
4a-7=-4 thì b=-7
a=3/4 (loại)
4a-7=28 thì b=1
a=35/4 (loại)
4a-7=1 thì b=28
a=2 (t/m)
4a-7=14 thì b=2
a=21/4 (loại)
4a-7=2 thì b=14
a=9/4 (loại)
4a-7=4 thì b=7
a= 11/4 (loại)
4a-7=7 thì b=4
a= 7/2 (loại)
Vậy (a;b)=(0;-4);(2;28)